Evaluation of new technology for intraoperative evoked compound action potential threshold measurements. - Tavartkiladze, George; Bakhshinyan, Vigen; Irwin, Colin (International Journal of Audiology, 2015)
Objective: To determine whether new technology for intraoperative evoked compound action potential (ECAP) threshold measurements-the CR120 Intraoperative Remote Assistant device-is comparable to the existing Custom Sound® clinical system, as well as assess test-retest accuracy of the systems. Design: Within subject, repeated measures comparative design. Study sample: ECAP data were collected from 81 pediatric subjects (41 females and 40 males). Results: The average ECAP threshold measurement time for the Custom Sound system was 6.2 minutes (SD = 1.0) versus 4.8 minutes (SD = 0.7) for the CR120 device. ECAP thresholds measured with Custom Sound and the CR120 device had an average Pearson product-moment correlation coefficient for all electrodes (N = 1724) of 0.92, p < 0.01; an average mean absolute difference of 6 CLs (SD = 6); and a 95% confidence interval of − 1 to 1 CLs. The test-retest results for Custom Sound and the CR120 device are also included. Conclusion: A significant reduction in the measurement time for ECAP thresholds was noted with the CR120 device. Furthermore, ECAP thresholds measured with the CR120 device are equivalent to Custom Sound within a clinically acceptable range.